Material Characteristics and Adoption Challenges Affecting Intention to Use Engineered Wood for Housing: The Role of Ecological Perception - Rosalia, Inten Persa; Larasati, Dewi; Pangestu, Roiswahid Dimas; Zahrah, Wahyuni; Aditra, Rakhmat Fitranto; Salamah, Hafshah (International Journal of Architecture and Urbanism, 2026)
Engineered wood has significant potential to support low-carbon construction in Indonesia; however, its adoption in the residential sector remains limited due to uneven knowledge distribution, concerns regarding durability, and limited ecological literacy. This study addresses the gap between the technical potential of engineered wood and its low level of acceptance by examining how material characteristics and adoption challenges influence user interest, with ecological perception considered as a mediating factor. A mixed-methods sequential explanatory design was employed, beginning with a qualitative phase involving 115 respondents through an open-ended online questionnaire, followed by a quantitative survey of 116 respondents. Data were analyzed using Exploratory Factor Analysis and multiple regression. The results show that knowledge of engineered wood remains segmented, with higher levels observed among highly educated respondents, formal-sector workers, and urban residents. Material perceptions are positively shaped by technical attributes such as strength, dimensional stability, and thermal performance, while concerns related to long-term durability and initial cost remain key barriers to adoption. User interest is influenced not only by technical understanding but also by ecological awareness and professional experience, underscoring the importance of social and psychological factors in material selection. These findings highlight the need for integrated educational and policy strategies that enhance sustainability literacy, strengthen technical confidence, and support the wider adoption of engineered wood in Indonesia’s low-carbon housing development.